Screening of protonstatin-1 (PS-1) analogs for improved inhibitors of plant plasma membrane H+-ATPase activity - Yang, Yongqing; Liu, Xiaohui; Wang, Xin; Lv, Wanjia; Liu, Xiao; Ma, Liang; Fu, Haiqi; Song, Shu; Lei, Xiaoguang (Frontiers in Plant Science, 2022)
We previously identified protonstatin-1 (PS-1) as a selective inhibitor of plasma membrane H+-ATPase (PM H+-ATPase) activity and used it as a tool to validate the chemiosmotic model for polar auxin transport. Here, to obtain compounds with higher affinity than PS-1 for PM H+-ATPase, we synthesized 34 PS-1 analogs and examined their ability to inhibit PM H+-ATPase activity. The 34 analogs showed varying inhibitory effects on the activity of this proton pump. The strongest effect was observed for the small molecule PS-2, which was approximately five times stronger than PS-1. Compared to PS-1, PS-2 was also a stronger inhibitor of auxin uptake as well as acropetal and basipetal polar auxin transport in Arabidopsis thaliana seedlings. Because PS-2 is a more potent inhibitor of PM H+-ATPase than PS-1, we believe that this compound could be used as a tool to study the functions of this key plant enzyme.